First Screening of Entomopathogenic Nematodes and Fungus as Biocontrol Agents against an Emerging Pest of Sugarcane, Cacosceles newmannii (Coleoptera: Cerambycidae) - (:unkn) unknown (My University, 2019)
Cacosceles newmannii (Coleoptera: Cerambycidae) is an emerging pest of sugarcane in South Africa. The larvae of this cerambycid beetle live within the sugarcane stalk and drill galleries that considerably reduce sugar production. To provide an alternative to chemical control, entomopathogenic nematodes and fungus were investigated as potential biological control agents to be used in an integrated pest management system. The nematodes Steinernema yirgalemense, S. jeffreyense, Heterorhabditis indica, and different concentrations of the fungus Metarhizium pinghaense were screened for efficacy (i.e., mortality rate) against larvae of C. newmannii. The different biocontrol agents used, revealed a low level of pathogenicity to C. newmannii larvae, when compared to control treatments.
Keywords: African Research